Strengthening RC structures using FRP spike anchors in combination with EBR systems. (1st February 2019) - del Rey Castillo, Enrique; Dizhur, Dmytro; Griffith, Michael; Ingham, Jason
Abstract: The use of Fiber-Reinforced Polymer (FRP) materials as Externally Bonded Reinforcement (EBR) to strengthen and/or repair existing Reinforced Concrete (RC) structures is widely documented, and various methods exist to increase the bond strength and/or ensure load-path continuity between FRP composites and the concrete substrate. The use of FRP anchors to increase the capacity of EBR systems offers a number of critical advantages compared to other existing methods. However, despite the significant amount of research previously undertaken on the topic a concise summary of the experimental performance of FRP anchors has not yet been reported. Consequently, a database consisting of five tables comprising the results from studies focused on testing isolated FRP anchors and four additional tables with results related to the use of FRP anchors in combination with FRP-EBR systems to strengthen and/or repair RC structures is presented. A number of tentative design models previously published for various failure modes are reported and reanalyzed in a critical way, and behavioral trends were identified as an effort to discern what models are ready to be used and what new further research is needed in the development of design guidelines for FRP anchors.